2019
DOI: 10.1002/adsu.201900047
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid Based on Glucose‐Derived Carbon Dots Functionalized with [Bmim]Cl for the Next Generation of Smart Windows

Abstract: The design of new advanced materials and technologies is essential for the development of smart windows for the next generation of energy-efficient buildings. Here, it is demonstrated that the functionalization of glucose-derived carbon dots with 1-butyl-3-methylimidazolium chloride results in a self-standing, water-soluble, viscous, reusable nanofluid with self-improving conductivity, thermotropy around 30-40 °C, and ultraviolet blocking ability. Its synthesis is straightforward, clean, fast, and cheap. At 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Ma et al [25] reported a novel electrolyte based on poly(ethylene oxide) (PEO) nanocomposite with oxygen-rich Cdots that exhibited a conductivity of 0.139 mS•cm −1 , a value significantly lower than that obtained here using ILs as the surface groups. Moreover, these nanofluids present a self-improving feature upon cycling [17,18], which is evident in Figure 3c. Upon four consecutive heating/cooling cycles, the % increase in the conductivity in Cdots/ [17,18].…”
Section: Nanofluid Characterizationmentioning
confidence: 96%
See 4 more Smart Citations
“…Ma et al [25] reported a novel electrolyte based on poly(ethylene oxide) (PEO) nanocomposite with oxygen-rich Cdots that exhibited a conductivity of 0.139 mS•cm −1 , a value significantly lower than that obtained here using ILs as the surface groups. Moreover, these nanofluids present a self-improving feature upon cycling [17,18], which is evident in Figure 3c. Upon four consecutive heating/cooling cycles, the % increase in the conductivity in Cdots/ [17,18].…”
Section: Nanofluid Characterizationmentioning
confidence: 96%
“…Moreover, these nanofluids present a self-improving feature upon cycling [17,18], which is evident in Figure 3c. Upon four consecutive heating/cooling cycles, the % increase in the conductivity in Cdots/ [17,18]. Usually, electrolytes tend to degrade upon consecutive cycling; however, in these nanofluids, we noted precisely the opposite trend (Figure 3b,c).…”
Section: Nanofluid Characterizationmentioning
confidence: 96%
See 3 more Smart Citations